Drug Therapy Problem: Prevalence and Associated Risk Factors Among Hypertensive Patient - Ibrahim, Umar Idris; Al-amin, Muhammad Chamo; Hassan, Abubakar Musa; Wada, Abubakar Sadiq; Jamil, Ahmad Kamal Ariffin Bin Abdul (International Journal of Membrane Science and Technology, 2023)
Drug therapy problem is an event involving drug therapy that actually or potentially interferes with the desired health outcomes. This study aimed to identify drug therapy problems encountered by hypertensive patients receiving care in BUK Clinic, Nigeria. It was a retrospective analysis of the medical records of adult hypertensive patients. A total of 206 patient folders were used for the study. The data were collected from the patient’s medical records using the Pharmaceutical Care Network Europe (PCNE) Classification tool Version 9.1 (PCNE, 2020). Data were analyzed using the IBM Statistical Product and Service Solutions (SPSS). The total number of drug therapy problem found was 314 of which majority was effect of drug treatment not optimal [P1.2] 155(49.4%) followed by adverse drug event [P1.3] 155(49.0%) and no effect of drug therapy despite correct use [P1.1] 5(1.6%) was the least type of drug therapy problem encountered. The major cause of drug therapy problem was inappropriate drug according to guidelines/formulary and inappropriate combination of drugs (C1.1 & C1.3) which account for 80(26.4%) of drug related problem. Prevalence of drug therapy problem was high (85.9%). Number of Antihypertensives on (P=0.022) and age(P=0.025) were significantly associated with increased drug therapy problem. Increased drug therapy problem can lead to increase in complications, increased hospital stays, emergency hospitalization and increased medical cost.